Emerging artificial intelligence (AI), risk to human rights? - Figueroa Gutarra, Edwin (2024)
Artificial Intelligence (AI) poses diverse challenges for human rights at the level of digital environments. Along with the inexorable advance of these rights, several risks arise – discrimination, replacement of human labor, forms of impact on human creativity, etc. – that must be faced through public policies that emphasize the promotion of ethical principles in the development of AI. These principles represent a point of balance between AI and human rights.